Production and characterization of cellulolytic enzymes from three fungi - A. Elmustafa, Amina; Abdel-Rahim, Awad M. (Gezira Journal of Engineering and Applied Sciences; مجلد 8 عدد 1 (2013), 2018)
Celluloses are carbohydrate polymers, much abundant as agricultural residues or wastes. They are resistant to enzymatic cleavage in most animals.  Researches around the world were therefore directed towards finding methods for hydrolyzing these compounds to obtain glucose. One such approach is enzymatic hydrolysis. Three fungi ( Trichoderma viride, Asperigillus niger and Penicillum digitatum ) were used for production of cellulase enzymes, in the present study, under laboratory conditions.  Two methods (reducing sugar and viscometry) were used for measuring the enzymetic activity. Carboxymethylcellulose (CMC) was used as a substrates for the enzyme activity. Different substrates were used for enzyme production . The results showed that A . niger and T. viride gave maximum production of cellulase enzyme after one week. While P. digitatum gave it after two weeks. Purification by ammonium sulphate precipitation,  showed that the maximum cellulase enzyme activity was at 60% concentration for the three fungi. By using gel electrophoresis, three bands were showing cellulolytic activity. This study showed the importance of fungi as sources of enzymes and recommends that more studies must be done in the field of biotechnology to produce more glucose from natural products by using fungi.